Age related content of different tissues in the lumbar spine paravertebral muscles with degenerative diseases - Radchenko, Volodymyr; Skidanov, Artem; Morozenko, Dmytro; Zmiyenko, Yuriy; Mischenko, Lyubov; Nessonova, Marina (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to determine the nature of age-related changes in paravertebral muscles in healthy volunteers and patients with degenerative diseases of the lumbar spine based on an analysis of the results of computed tomography. Methods: the results of a survey of 129 patients (53 men, 76 women), operated for lumbar spine degenerative diseases, and 11 healthy volunteers, as well as computed tomography scans of 93 individuals aged 6 to 21 years, were analyzed. The relative content of fat, muscle, and connective tissues in the paravertebral muscles of lumbar spine was determined on the basis of their X-ray density on axial computed tomography scans using an original computer program with an accuracy of 87.85 %. Correlation analysis was performed to evaluate the results. Results: until the end of growth, the content of muscle tissue does not change significantly with age, but the percentage of connective tissue increases. At the end of the growth, the content of muscle tissue decreases significantly, and with age, against a background of a marked increase in the fat percentage. The influence of age on the content of connective tissue is less pronounced. Until the end of growth, as well as after the change, more pronounced in the straightening of the spine and multi-parted muscles. Patients with lumbar spine degenerative diseases have a moderate decrease in muscle tissue and an increase in fat with age in all muscles. However, the decrease in the relative content of muscle tissue is more pronounced in the muscles that straighten the spine, and the increase in the relative content of fat and connective muscle in the multifidus and lumbar muscles. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> with age in the paravertebral muscles, the content of muscle tissue decreases on the background of an increase in connective and fat.